2014
DOI: 10.1111/jph.12325
|View full text |Cite
|
Sign up to set email alerts
|

Bougainvillea Shoot Proliferation, a New Disease Induced by Distinct Phytoplasmas

Abstract: Bougainvillea‐potted plants exhibiting typical phytoplasma‐induced symptoms, characterized by foliar chlorosis, shoot proliferation, leaf and bract deformations, and decline were observed in commercial nurseries, located in the state of São Paulo, Brazil. In this study, PCR assays using group‐specific primers revealed that phytoplasmas affiliated with the groups 16SrI and 16SrIII were associated with symptomatic plants. Molecular analysis based on conventional and virtual RFLP patterns and similarity coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…Surveys have revealed that the diverse representatives of the 16SrIII group are those most frequently found in cultivated and uncultivate species, such as Brassica oleracea (Rappussi et al, 2012;Eckstein et al, 2013;Amaral-Mello et al, 2011); Manihot esculenta Souza et al, 2014); Solanum melongena; Passiflora edulis, Cucurbita pepo, Sechium edule, Solanum licopersicum, Melia azedarach, Catharanthus roseus and Euphorbia pulcherrima (Amaral-Mello et al, 2011); Leonurus sibiricus ; Celosia sp. (Eckstein et al, 2012); Bougainvillea spectabilis (Silva et al, 2014); and Brachiaria decumbens (Fugita et al, 2017). Interestingly, the subgroup 16SrIII-F had not been reported in Brazilian territory.…”
Section: Resultsmentioning
confidence: 99%
“…Surveys have revealed that the diverse representatives of the 16SrIII group are those most frequently found in cultivated and uncultivate species, such as Brassica oleracea (Rappussi et al, 2012;Eckstein et al, 2013;Amaral-Mello et al, 2011); Manihot esculenta Souza et al, 2014); Solanum melongena; Passiflora edulis, Cucurbita pepo, Sechium edule, Solanum licopersicum, Melia azedarach, Catharanthus roseus and Euphorbia pulcherrima (Amaral-Mello et al, 2011); Leonurus sibiricus ; Celosia sp. (Eckstein et al, 2012); Bougainvillea spectabilis (Silva et al, 2014); and Brachiaria decumbens (Fugita et al, 2017). Interestingly, the subgroup 16SrIII-F had not been reported in Brazilian territory.…”
Section: Resultsmentioning
confidence: 99%
“…The bar represents a phylogenetic distance of 1% and India (Bongnam et al 2007;Chung 2008;Min and Hu 2009;Kumar and Byadgi 2012;Raj et al 2007), 16SrII from India (Yadav et al 2015) and 16SrIII from China (Chung 2008) were identified in chrysanthemum crops (Two different groups of phytoplasmas were reported from jasmine, 16SrI from Italy (Marzachì et al 1999) and 16SrII group from Oman (Al-Zadjali et al 2007); however, in India only one report is available on jasmine belonging to 16SrXI group from Jaipur, Rajasthan (Madhupriya et al 2015). In bougainvillea, two phytoplasma groups (16SrI-B and 16SrIII) were reported from Brazil (Silva et al 2014); however, no reports are available on occurrence of phytoplasma infection on bougainvillea from India. In Chinese aster, two groups belonging to 16SrI and 16SrII were reported from Korea (Win et al 2011), Germany (Marcone et al 2000) and USA (Zhang et al 2004;Lee et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Bougainvillea spectabilis : foliar chlorosis, shoot proliferation, leaf and bract deformations and decline (Silva et al., 2015)…”
Section: Appendix a – Symptoms On Plants Other Than Solanum Tuberosummentioning
confidence: 99%